Pengembangan Trainer Pengontrolan Elektromagnetik Pada Jurusan Teknik Instalasi Tenaga Listrik Di Smk Negeri 2 Peureulak – Aceh Timur - Hendri Pratama (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
Department of Electrical Installation Engineering at SMKN 2 Peureulak is part of educational institutions that graduated the expertise and creativity students. Competencies obtained by students who tailored to industry-based curriculum criteria. Thus, they have ready-made expertise through the learning process. Learning tools or media used in the learning process were the important role to achieve the learning objectives. Therefore, the learning media used is very influential on the intensity of learners on the subject matter. Trainers are designed to implement a modular concept that each component is made separately, equipped with component names, symbols and manuals of use so that it can easily be introduced to components, use and facilitate understanding of the concept of electromagnetic control installed. The design and manufacture of this trainer through several stages of the material and information gathering stage, the design of each component module, the design of sliding frames and storage boxes, tool making, tool testing and the last manual book making. There are three steps to determine the eligibility of the electromagnetic control trainers, namely (1) the manufacture of electromagnetic control trainers (2) the trainer feasibility test (3) product testing. In this study, the respondents are 3 teachers and 23 students technical expertise program electrical installation in SMK Negeri 2 Peureulak. Research instrument used in the form of questionnaire of media feasibility test, student response questionnaire and observation sheet. The results showed that the electromagnetic control trainer that has been developed feasible to be used as instructional media of electromagnetic control in electrical engineering skill program at SMKN 2 Peureulak. The achievement of feasibility of trainer was performed from the result of feasibility analysis by expert team which get the percentage of 81% with good category, and the result of student response to the electromagnetic control trainer get the percentage of 87% with very good category. There was a significant difference between the learners' learning outcomes between before and after using trainers, where the average practice value before using the trainer was 77.81 and after trainer use increased to 82.30.